2020
DOI: 10.1007/s00227-019-3626-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding, stables isotopes, and tracking: unraveling the trophic ecology of a winter-breeding storm petrel (Hydrobates castro) with a multimethod approach

Abstract: stables isotopes, and tracking: unraveling the trophic ecology of a winter-breeding storm petrel (Hydrobates castro) with a multimethod approach. Marine Biology 167 ( 14) , -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…Technological advances now provide an opportunity to investigate the linkages between individuals' spatial movements, habitat use, and diet, not previously possible for smaller terrestrial species (Carreiro et al., 2020; Groom et al., 2017). Investigating these linkages by combining multiple modern techniques will allow for deeper insights into the ecology of difficult‐to‐study species than would be possible from any one technique alone (Groom et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances now provide an opportunity to investigate the linkages between individuals' spatial movements, habitat use, and diet, not previously possible for smaller terrestrial species (Carreiro et al., 2020; Groom et al., 2017). Investigating these linkages by combining multiple modern techniques will allow for deeper insights into the ecology of difficult‐to‐study species than would be possible from any one technique alone (Groom et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Males exhibited higher δ 13 C and δ 15 N values, and larger isotopic niches compared to females, presumably caused by spatial sexual segregation and exploitation of areas of contrasting environmental conditions [ 34 ]. In the Madeiran storm-petrel ( Hydrobates castro ) δ 15 N values differed between sexes during the non-breeding period, with females having lower δ 15 N values than males, possibly caused by intersexual differences in distribution during the non-breeding season, or as a result of differences in diet between sexes or differences in the relative amount of different prey taken [ 35 ]. However, in Canadian LSP populations, no sexual isotopic segregation was found [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on several Procellariiformes species showed that in larger, size-dimorphic, species δ 13 C values in females were higher than in males, suggesting a more northerly distribution, while no isotopic differences were found in species not displaying sexual dimorphism [ 33 ]. In storm-petrels, sexual isotopic segregation was previously found in several species [ 34 , 35 ], but not all [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…and little bustards (Tetrax tetra) 38,39 . Significant sex-dependent food preference or intersexual plasticity in the diet has been observed in different animals, such as storm petrels, oystercatchers, grouses, crows, minks, bats, and capuchins [40][41][42][43][44][45][46] . An alternative explanation for individual dietary variation is the foraging proficiency of individuals.…”
Section: Dietary Composition Variation Between Roosting Groupsmentioning
confidence: 99%